Analysis of Learning of Entrepreneurship Courses in the History Education Study Program Universitas Negeri Semarang - Agus Rahmat Mahmudi; Kurniawati Kurniawati; Andy Suryadi (Universitas Hamzanwadi, 2025)
This research has specific objectives aimed at analyzing the mechanisms involved in the learning process of entrepreneurship courses, particularly in the context of the History Education program. The chosen research methodology is qualitative, employing a case study approach. Data collection was conducted through direct observation, interviews or interactive question-and-answer sessions, and documentation. The findings of this research reveal that the complex mechanisms within the entrepreneurship learning process in the History Education program have been effectively established, incorporating methods and learning media that are deemed to meet the necessary requirements. However, challenges identified during the learning process primarily concern time allocation and students' comprehension of entrepreneurship concepts. Thus, the entrepreneurship course implemented in the History Education program plays a significant role and is regarded as effective in fostering efforts to cultivate a new generation of young entrepreneurs.